Instilling Religious Values Through Songs in Forming Social Bonds at West Kalimantan State Middle Schools - Mastri Dihita Sagala (Qalamuna)
Instilling religious values is important to implement early, even during children's development and growth. Music, which has numerous benefits, can be an effective strategy in instilling those religious values. This research discusses the instillation of religious values implemented through singing activities using the "Mars Gembira Bergerak." The focus and data of the research were gathered at SMPN 2 Bengkayang, West Kalimantan. This song was created by the headmaster, who also has an interest and talent in the field of music. This research is descriptive and adopts a qualitative approach. Data were obtained from observations, interviews, and documentation of the song, which were transcribed to understand the lyrics and meaning of the song. The primary source is Mr. Marsel Marselius, the Headmaster and the song's creator. The triangulation technique was used to determine the educational strategy. The research results show that this song contains values of responsibility, enthusiasm, independence, creativity, and wisdom. It is important to sing while performing rhythmic movements so that this can lead to the creation of an interactive and enjoyable learning environment. Engaging social education will encourage active participation from students, fostering a sense of togetherness and strengthening social bonds among them. Through music, Islamic values such as the spirit of struggle, cooperation, and love for the homeland can be conveyed in a more engaging and easily understood manner by the students.